Congenital epulis: A rare benign baby lump - Xavier, Rose; Ajitha, M; Manoj, V C (Indian Journal of Child Health, 2015)
Congenital epulis is a rare congenital tumor affecting the oral mucosa. It is usually seen in females and has no known syndromic association. It may cause the interference to feeding or airway obstruction, thus presenting as an emergency. Visually, it causes a lot of undue stress and anxiety to the parents and relatives. Multiple epulis occurs only in 10% of cases. Recurrence of the tumor, malignant change, or damage to dentition is not seen post-excision. Clinicians, particularly those working in the tertiary health care facilities, should be aware of this benign and easily treatable tumor of the neonate.